An Assessment of Heavy Metals in Synodontis Clarias (Linnaeus, 1766) from Ikpoba Reservoir, Benin City, Nigeria - OM Wangboje; JAO Oronsaye (Journal of Applied Sciences and Environmental Management)
This study determined the concentrations of Cd, Mn, Cu, Pb, Zn and Cr in Synodontis clarias (Linnaeus, 1766) and water from Ikpoba Reservoir, Benin City, Nigeria, in order to ascertain the magnitude of impact by these heavy metals on the resources of the investigated ecosystem. The mean concentrations of the heavy metals in fish were Cd (0.01mg/kg), Mn (2.38 – 2.54mg/kg), Cu (0.09 – 0.16mg/kg), Pb (0.03 – 1.25mg/kg), Zn(10.45 – 15.38mg/kg) and Cr (0.01 – 0.02 mg/kg). The mean concentrations of the heavy metals in water were Cd (0.01mg/l), Mn (0.02 – 0.03mg/l), Cu (0.19 – 0.32mg/l), Pb (0.05 –0.08mg/l), Zn (98.70 – 132.38mg/l) and Cr (0.02 – 0.05mg/l). The mean concentrations of Pb and Zn in fish, were significantly different (P < 0.05) between stations while the mean concentrations of Cu and Zn in water, were significantly different (P<0.05) between stations. Manganese was bioaccumulated by the fish at all the stations while Pb was bioaccumulated by the fish at all the stations except at the low lift pump station. Heavy metal concentrations in fish and water were discussed with reference to the World Health Organisation (WHO) limits for food fish and water. It was advocated that regular monitoring of heavy metals in fish and water in the Reservoir be carried out in other to curtail further negative impacts